The effect of milk urea nitrogen on milk composition in holstein dairy cows - Tugay Ayaşan; Hatice Hızlı; Ertan Yazgan (Eurasian Journal of Veterinary Sciences)
Aim: The objective of this study was to evaluate the effects of milk urea nitrogen on milk composition. Materials and Methods: According to their milk urea nitrogen (1. Group: x<22.73 mg/dL; 2. Group: x>22.73 mg/ dL), the Holstein cows were divided into two groups as 36 animals per group. Results: In the experiment, milk urea nitrogen were affected solids-non-fat, density and urea significantly (p<0.05); a significant correlation (r=0.140, p<0.045) was recorded between milk urea nitrogen and solids non fat and density (r=0.186, p<0.007). Conclusion: The findings obtained from in this study are important that in terms of to reveal effects of milk urea nitrogen on milk composition and to be used as a source prospective investigations.